ЩОДО ЗАХИСТУ ПРАВА ДЕРЖАВИ НА ОТРИМАННЯ ДИВІДЕНДІВ - Pereyaslavska, Y.A. (Економіка та право, 2010)
The paper analyzes legal regulation of the state’s rights to getting dividends and its practical aspects, as well as reveals legal problems concerning protection of the above rights. This problem is often difficult to solve because of inadequate juridical practice of both economic courts and administrative ones when settling disputes.